Association of the 25(OH) vitamin D status with upper respiratory tract infections morbidity in water sports elite athletes - Umarov, J.; Kerimov, F.; Toychiev, A.; Davis, N.; Osipova, S. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The aim of this study is to determine seasonal changes of total serum 25(OH) vitamin D (VD) concentration and its influence on upper respiratory tract infection (URTI) morbidity among water sports elite athletes. METHODS: The study was planned as a prospective, non-interventional, observational study. Study participants included 40 elite athletes and 30 control individuals. Serum levels of 25(OH) VD and TNF-alpha, IFN-gamma, IL-4 and IL-6 were detected by ELISA technique. Frequency of acute URTI in participants was determined by medical cards and self-reported questionnaire during the year. RESULTS: VD deficiency/insufficiency dominated in both groups of elite athletes, especially in synchronized swimmers (100%) in comparison with the control individuals (63.3%) (P=0.05). Prevalence of VD deficiency/insufficiency depends on the season, but independently on the season the highest values were observed among athletes. VD sufficiency was detected in 30% and 13.3% of the control individuals in August and February and only in 10% of swimmers in August. More than 3 episodes of URTI were detected only in elite athletes in winter-spring. The elevation of TNF-alpha, IL-4, IL-6 and decrease of IFN-gamma levels were detected in all athletes, but they were more expressed in swimmers. CONCLUSIONS: VD insufficiency is quite pronounced among elite athletes engaged in synchronized swimming and swimmers. It is accompanied with a decrease of IFN-gamma, increase of TNF-alpha, IL-4 and IL-6 level, and elevation of URTI morbidity. Seasonal monitoring and correction of the VD level for normalization of cytokine profile and decrease of URTI morbidity is definitely advised.